Detecting and interpreting financial stress in the euro area - Marianna Blix Grimaldi (European Central Bank (ECB), 2010)
There is a need to find better models and indicators for large disruptive events, not least in order to be more prepared and mitigate their effects. In this paper we take a step in this direction and discuss the performance of a financial stress indicator with a specific focus on the euro area. As far as we know, our indicator is the first attempt to develop an indicator of financial stress with a specific focus on the euro area. It is also the first to exploit the information contained in central bank communication to help measure stress in financial markets. For use in real time, the indicator is able to efficiently extract information from an otherwise noisy signal and provide information about the level of stress in the markets.
Keywords: E44; E50; G10; 330; behavioural finance; central bank communication; Financial stress; Leading Indicator; logit distribution; Wirtschaftsindikator; Finanzkrise; Finanzsektor; Geldpolitik; Anlageverhalten; Eurozone; EU-Staaten